THE USE OF DUOLINGO APPLICATION TO INCREASE STUDENTS’ VOCABULARY MASTERY - Kristyanti Adhelheid Borang; Mister G. Maru; Rinny S. Rorimpandey (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study’s objective is to find out if the Duolingo Application could aids students to improve their vocabulary mastery especially adjective. This research is quantitative and using pre-test and post-test design through a written test. The subject of this study were 31 students from SMP Negeri 1 Manganitu class 8 B. According to the data obtained, the mean Pre-Test score is 43,32, with the greatest Pre-Test score is 83 and the lowest is 10, and the highest Post-Test score is 97 and the lowest is 63, and the Post-Test’s average score is 79.80. Significant improvements can be noted in this data, and it can be concluded that the use of duolingo application successful for increase students’ vocabulary mastery